2004
DOI: 10.1017/s0952836904005552
|View full text |Cite
|
Sign up to set email alerts
|

Variation in harem size of red deer (Cervus elaphus L.): the effects of adult sex ratio and age‐structure

Abstract: The relationships among harem size, adult sex ratio (proportion of males > 5 years in the adult population, i.e. males > 5 years plus females > 2 years) and male age-structure of red deer Cervus elaphus were investigated in La Petite Pierre National Reserve (PPNR) in France. We tested whether: (1) increasing adult sex ratio leads to a decrease in harem size along with an increase in the number of harems within a given rut period; (2) whether participation of sub-adult males in mating activities increases with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 68 publications
1
26
1
Order By: Relevance
“…Contrary to our findings, the decrease of female group size with the increase of male numbers has previously been reported in several ungulates, e.g. red deer (BONENFANT et al 2004) and wapiti (BENDER 1996). Also, for reindeer, L' ITALIEN et al 2012) reported that the mean number of females per mating group decreased with an increase in male percentage, possibly because of the energetic costs associated with keeping away competitors, while herding females.…”
Section: Group Sizecontrasting
confidence: 99%
“…Contrary to our findings, the decrease of female group size with the increase of male numbers has previously been reported in several ungulates, e.g. red deer (BONENFANT et al 2004) and wapiti (BENDER 1996). Also, for reindeer, L' ITALIEN et al 2012) reported that the mean number of females per mating group decreased with an increase in male percentage, possibly because of the energetic costs associated with keeping away competitors, while herding females.…”
Section: Group Sizecontrasting
confidence: 99%
“…The mating system of the PPNR population is polygynous, with males competing to dominate harems of oestrous females between September and October (Bonenfant et al 2004). Telemetry work has suggested that dispersal is male biased and that female emigration is rare, leading to a close spatial association between female relatives in the study area (Hamann et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Telemetry work has suggested that dispersal is male biased and that female emigration is rare, leading to a close spatial association between female relatives in the study area (Hamann et al 2003). After the change in the management regime, the increase in the number of older males in the population led to a reduction in the variance in male reproductive success, as the number of the harems increased, but their size decreased (Bonenfant et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Human hunting can influence reproductive behavior of ungulates by skewing the sex ratio and/or by removing certain individuals from a population (Bonenfant et al, 2004; Mysterud et al, 2003). Such changes can profoundly impact mating dynamics (Mysterud, Coulson & Stenseth, 2002).…”
Section: Discussionmentioning
confidence: 99%